2010
DOI: 10.1177/1059601109360389
|View full text |Cite
|
Sign up to set email alerts
|

Gossip in Organizations: Contexts, Consequences, and Controversies

Abstract: This article examines the key themes surrounding gossip including its contexts, the various outcomes (positive and negative) of gossip as well as a selection of challenges and controversies. The challenges which are highlighted revolve around definitional issues, methodological approaches, and ethical considerations. Our analysis suggests that the characteristics and features of gossip lend itself to a process-oriented approach whereby the beginning and, particularly, end points of gossip are not always easily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
144
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 67 publications
6
144
1
5
Order By: Relevance
“…Overall, the findings have enriched the understanding of the link between gossip and ECN over and above what we know from previous empirical studies of gossip (Kurland & Pelled, 2000;McAndrew et al, 2007). Compared to the previous studies which focused on the function of gossip (Foster, 2004;Michelson et al, 2010) and gossip influence (Cole & Dalton, 2009;DiFonzo & Bordia, 2007), our research has provided a further and more systematic perspective to interpret the gossip -ECN relationship.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Overall, the findings have enriched the understanding of the link between gossip and ECN over and above what we know from previous empirical studies of gossip (Kurland & Pelled, 2000;McAndrew et al, 2007). Compared to the previous studies which focused on the function of gossip (Foster, 2004;Michelson et al, 2010) and gossip influence (Cole & Dalton, 2009;DiFonzo & Bordia, 2007), our research has provided a further and more systematic perspective to interpret the gossip -ECN relationship.…”
Section: Discussionmentioning
confidence: 78%
“…In the workplace, gossip is often regarded as idle talk about other colleagues who are absent and, interestingly, researchers seem to have mixed views of how gossip actually gets started and the role it plays. Michelson, Iterson, and Waddington (2010) suggest that gossip is a dynamic process and the effects of gossip depend on the interaction between gossiper, listener/respondent, and target, i.e. the gossip triad.…”
Section: Introductionmentioning
confidence: 99%
“…(For an exhaustive list of definitions of gossip in the literature, see Michelson, van Iterson, and Waddington 2010:379). For our purposes here, we adopt a broad definition used in recent research (e.g., Feinberg et al 2012;Foster 2004;Michelson, van Iterson, and Waddington 2010)-evaluative talk between two or more persons about absent third parties.…”
Section: Gossip In Professional Contextsmentioning
confidence: 99%
“…Problematically, however, although gossip can strengthen relationships between the gossiper and recipient, it has potential to damage relationships with the talked about third party (Michelson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…From this research a number of core features are consistently reported. For conversation to be considered gossip it should be triadic (Michelson et al, 2010), evaluative (DiFonzo & Bordia, 2007), remedial (Guendouzi, 2001) and is typically (but not exclusively) negative (Noon & Delbridge, 1993). It is noted that the talked about other should be non-present (Foster, 2004) and that there are social sanctions for engaging in gossiping (McDonald et al, 2007).…”
Section: Introductionmentioning
confidence: 99%